Is The Essential Newborn Care Package an Effective Intervention for Reducing Neonatal Sepsis In India? - Masters, Rebecca (2008)
Background: Neonatal sepsis is an important cause of morbidity and mortality in India. Neonatal health programmes such as the Essential Newborn Care Package focus on preventative and curative care for the reduction of neonatal sepsis. However, neonates continue to die as a consequence of sepsis, many of which deaths are preventable. This critical review examines the factors that impact on neonatal sepsis and evaluates the effectiveness of this package aimed at preventing neonatal death.